Correlação do doppler espectral articular com atividade inflamatória na artrite reumatóide - Bisi, Melissa Cláudia (2016)
Introduction: Ultrasonography (US) is an useful tool for evaluation of synovial vascularization and proliferation in rheumatoid arthritis (RA). Differently from US power Doppler (PD), the resistive index (RI) of spectral Doppler (SD) provides a quantitative analysis of vascular inflammation, but its utility in the ultrasonographic evaluation of RA activity has not been established. Objetives: To associate the RI with US parameters of synovitis and disease activity in patients with established RA. Methods: Consecutive pD-positive RA patients were included in a prospective cross-sectional study. Disease activity and disability were evaluated using the Disease Activity Score in 28-joints (DAS28) and Health Assessment Questionnaire (HAQ), respectively. Gray scale (GS) synovitis, PD and SD analysis were performed by one of two examiners in wrists, second and third metacarpophalangeal, and proximal interphalangeal joints. The 10 joint-GS and -PD scores and the mean RI were then calculated. Weighted kappa values were employed to assess interobserver reliability. Results: out of 112 patients scanned initially, 95 patients with PD signal were included (median duration of disease, 7 years and mean DAS28, 4.32 ± 1.66). Weighted kappa values in real-time US were 0.77 for synovitis, 0.87 for PD and 0.68 for RI. There was a significant association of 10 joint-GS and -PD with swollen joints count (rs = 0.54, p <0.001 and rs = 0.39, P <0.001, respectively). There were no significant correlations of the RI with 10-joint- GS, 10-joint-PD, DAS28, joint counts or HAQ (P>0.10 for all tests). Conclusion: Spectral Doppler RI did not correlate to any US or clinical parameters of disease activity in our sample of established RA patients. The addition of the RI score does not seem to improve US performance in this scenario.